THE IMPACT OF SMOKING ON CARDIOVASCULAR HEALTH. (Journal of Universal Science Research, 2023)
We all know that tobacco products, including cigarettes, are an undesirable tool that seriously harms human health. It would be useful to mention once again how smoking harms a person's health and those around them.